Faktor Pendorong Perusahaan Melakukan Transfer Pricing - Siti Aliyah; Ela Amelia (Jurnal Rekoginisi Ekonomi Islam, 2023)
Abstract This study aims to measure and analyze the effect of taxes, foreign ownership, company size and bonus mechanisms on transfer pricing in manufacturing sector companies listed on the Indonesia Stock Exchange in 2017-2020. The analytical method used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing using the SPSS application. Determination of the sample in this study using purposive sampling technique so that the number of research samples obtained is 160 companies. The results of this study indicate that taxes have a positive effect on transfer pricing. This means that the higher the tax that must be paid, the more transfer pricing will increase. Foreign ownership has no effect on transfer pricing. This means that high or low foreign ownership will not increase transfer pricing. Firm size has a positive effect on transfer pricing. This means that the larger the size of the company, the more transfer pricing will increase. The bonus mechanism has no effect on transfer pricing. This means that the high or low bonus mechanism will not increase transfer pricing.